Salivary gland tumors in a Brazilian population: a retrospective study of 124 cases - Vargas,Pablo Agustin (2002)
Salivary gland tumors constitute a highly heterogeneous histopathologic group. There are few epidemiological studies of large series of benign and malignant salivary gland tumors in Brazil. MATERIAL AND METHODS: Hospital records of 124 patients with salivary gland tumors diagnosed from January 1993 to December 1999 were reviewed. The patients were analyzed according to gender, age, size, location, and histopathology of the tumor. RESULTS AND CONCLUSIONS: Patients with benign and malignant tumors presented with a mean age of 47.7 and 48.8 years, respectively. The frequency of benign tumors was 80% (n = 99) and malignant tumors 20% (n = 25). Tumors were localized in the parotid gland 71% (n = 88), in the submandibular gland 24% (n = 30), and in the minor salivary glands 5% (n = 6). The most common benign tumors were pleomorphic adenoma in 84% (n = 84) and Warthin's tumor in 13% (n = 13). Among malignant tumors, mucoepidermoid carcinoma was the most common in 52% (n = 13), adenoid cystic carcinoma occurred in 20% (n = 5), and carcinoma ex pleomorphic adenoma was detected in 12% (n = 3).